A boy with bird-like facies and ataxia: Cockayne syndrome - Vishalakshi S Pandit (Wolters Kluwer Medknow Publications, 2018)
Introduction: Congenital photosensitive disorders are a group disorders presenting with photosensitivity, short stature (SS), systemic manifestations and susceptibility to malignancy. These include Bloom syndrome, Cockayne syndrome (CS), Rothmund-Thompson syndrome, etc. Early identification and differentiating the syndrome from other congenital disorder is essential as the prognosis of each disorder differs. Case Report: A 4year-old-boy presented with photosensitive rash over the butterfly area of the face. He had history of delayed developmental milestones. His height and weight for his age were below the first percentile. On examination, patient had microcephaly, bird-like facies including sunken eyes, pinched nose, cachectic physique, ataxia and flexural contractures at elbow, knee and ankle joints. Ophthalmic examination showed pigmentary retinopathy on fundoscopy. CT scan of brain revealed bilateral basal ganglia calcification and evidence of premature mild cerebral atrophic changes. On the basis of clinical and lab investigations, we diagnosed this case as CS. Discussion: CS is a rare AR disorder characterized by normal prenatal growth with the onset of growth and developmental abnormalities in the first two years. They have SS, sexual immaturity, and/or retinal pigmentation. Diagnosis of the CS is made by characteristic clinical features specific to this, but the definitive diagnosis is achieved by laboratory investigations such as cytogenetic, biochemical and molecular methods. Although there is no specific treatment, avoidance of sun exposure and protection by sunscreens can help prevent some of the cutaneous eruptions associated with photosensitivity.